2021
DOI: 10.1371/journal.pone.0248928
|View full text |Cite
|
Sign up to set email alerts
|

Moral foundations theory, political identity, and the depiction of morality in children’s movies

Abstract: Children’s movies often provide messages about morally appropriate and inappropriate conduct. In two studies, we draw on Moral Foundations Theory (MFT) to derive predictions about actual depictions of morality, and people’s preferences for different moral depictions, within children’s movies. According to MFT, people’s moral concerns include individualizing foundations of care and fairness and binding foundations of loyalty, authority, and sanctity. Prior work reveals that although there are political differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Gehman et al adopted a focus on children's movies, specifically examining three movies, with the aim of identifying the differences in moral foundations between heroes and villains [37]. The presence of moral foundations was investigated by having a group of human coders fill out the Moral Foundations Questionnaire for each character under analysis.…”
Section: Moral Foundations Theory In Media Analysismentioning
confidence: 99%
“…Gehman et al adopted a focus on children's movies, specifically examining three movies, with the aim of identifying the differences in moral foundations between heroes and villains [37]. The presence of moral foundations was investigated by having a group of human coders fill out the Moral Foundations Questionnaire for each character under analysis.…”
Section: Moral Foundations Theory In Media Analysismentioning
confidence: 99%
“…It is also likely that some of these cultural differences in moral values may be reflected in the media of their respective cultures, such as TV shows. For example, a content analysis of American popular children's movies by Gehman et al, (2021) revealed that the heroic characters were depicted as abiding by and promoting more individualizing moral values (i.e., care and fairness) and less so of binding moral values (i.e., loyalty, authority, and sanctity) compared to the villains. The villains, on the other hand, were promoting or endorsing binding moral values more and less individualizing foundations.…”
Section: Valence Of Moral Principles In French and Spanish Televisionmentioning
confidence: 99%